Borate ester endcapped fluorescent hyperbranched conjugated polymer for trace peroxide explosive vapor detection1. Issue 38 (30th April 2015) - Chen, Lei; Gao, Yixun; Fu, Yanyan; Zhu, Defeng; He, Qingguo; Cao, Huimin; Cheng, Jiangong
<x xml:space="preserve">Abstract</x> The hyperbranched polymer S1/ZnO nanorod array composite is very promising for a highly sensitive fluorescence device for detecting peroxide explosives.